Impact of Coffee Production and People’s Household Income: A Case Study of Kibatsi Sub-County in Ntungamo District. - Oumo, David (Kabale University, 2024)
The purpose of this study was to find out the effects of coffee farming on household income, a case study of Murama Parish in Kibatsi Sub-County Ntungamo District. The objectives of the study were to assess the contribution of coffee farming to the income status of the people in Murama Parish, to find out whether coffee farming has contributed to the level of assets, and to establish whether coffee farmers have faced challenges. The study used primary data in its analysis and the researcher used descriptive modes of analysis using mainly quantitative methods of data collection to capture data. Data was collected using research questionnaires where the researcher was asking the questions on the questionnaire and noting down the respondents' answers. The findings revealed that the fanning of coffee has enabled the farmers to improve their standards of living since they earn money from the sale of coffee which has enabled farmers to pay school fees for their children in institutions of higher learning. The production of coffee has created employment opportunities for the people in the district especially the youth who are working in the small-scale coffee factories in the area and because of this coffee has become the sole source of income for many people in this area. The researcher recommends that the Government should increase the budget allocation on agriculture since most of the rural people depend on agriculture as their sole economic activity. This improved the economic welfare and development of rural people, Government through the Ministry of Trade should look for an international market for Uganda's coffee as this increased the prices of Uganda's coffee and the incomes of the rural people which gave farmers the ability to pay school fees for their children.